Inhibiting Back Pain and Enhancing Comfort During Pregnancy with The Power of Endorphin Massage - Surti Anggraeni; Miskiyah Miskiyah (Poltekkes Kemenkes Palu, 2023)
Back pain and anxiety during pregnancy can cause discomfort and interfere with activities in meeting daily needs. Endorphin massage is known to reduce back pain and make a person calmer so that it can reduce anxiety, but research on the effect of endorphin massage in dealing with back pain and anxiety is still minimally reviewed. The study aims to should be to find out the effect of endorphin massage for back pain and anxiety in third trimester pregnant women. The one-group pretest-posttest research method used a quasi-experimental design involving 42 respondents from 2 selected villages using a purposive sampling technique. The endorphin massage intervention was carried out 18 times with 2 observations, during the pretest and after the end of the intervention 18 times. After the analysis using the t-test, it is known that endorphin massage affects reducing back pain and anxiety in pregnant women. The analysis's findings demonstrated that there was an intervention effect on anxiety and back pain, with a p-value of 0.000, compared to a p-value of 0,042 for the control group. It was concluded that there is influence of endorphins to inhibiting back pain, enhancing comfort during pregnancy and it is very important to educate pregnant women about physical and psychological discomfort so that they can be anticipated in carrying out their daily activities. It is also recommended to consider the presence of the husband when implementing this activity.